PERAN MASYARAKAT MADANI MEWUJUDKAN CLEAN GOVERNMENT: PEMERINTAHAN YANG BEBAS KORUPSI KOLUSI DAN NEPOTISME - Dwi Martiningsih (LP3M IAI Al-Qolam Malang, 2018)
Corruption, Collusion and Nepotism (KKN) are social diseases that have long infected the nation and state of Indonesia. This paper conveys the social movement theory in the effort to create a government free from KKN through strengthening the role of masyarakat madani (civil society). The Jenkins and Klandermans’ diagram of the relationship of social movements with the state and the political system illustrates the problem of a three-way relationship between social movements, political representation and the state. The issue is the extent to which opportunities represented by political representatives in social movements, the impact of social protests on political parties and official political processes, as well as the implications of these relations in modern democracies. In this case, the social movement's chances through the 1998 reforms have been able to undermine the authoritarian New Order regime, a good start for the creation of democracy in Indonesia. However, it turns out that KKN disease that has been rooted to create systemic corruption (institutional entry) creates its own difficulties in eradication. Civil society as an alternative to social forces should be encouraged to play a role in solving the chaotic reform of the Indonesian bureaucracy. The role of civil society through NGOs, intellectuals, students, workers or labours, mass organizations, religious leaders, social media, press and other elements of society are expected to make the government more assertive in enforcing the law and crack down on KKN actors according to MPR XI / 1998, Anti-Corruption Law, as well as other supporting regulations that have been created. Law enforcement agencies, including POLRI, KPK, Judicial Commission are expected to play a role. This is of course with the participation of civil society as a control force that offsets the strength of government in upholding truth and justice. Keywords: civil society, social movements, KKN (Corruption, Collusion, and Nepotism), clean government.